Dampak Discount Promotion pada Platform E-Commerce terhadap Perilaku Impulsive Buying - Areta, Tiara Dini; Nadia Khairina (Universitas Negeri Malang, 2024)
The more advanced the times, the more advanced the development of technology in it. The rapid development of technology makes it easier for someone to find and provide the latest information. As a result of technological developments, it also affects changes in the way individuals carry out the transaction process. Technological developments and internet access are more widely used by Gen Z. There are some assumptions that shopping online provides more benefits than shopping in person. The purpose of this study is to determine whether discount promotion in E-commerce platform has an influence on impulsive buying and to determine the impact of this. In the research conducted, the author adopted a qualitative method using an open-ended questionnaire technique to review Gen Z who use e-commerce platforms for shopping. The results show that respondents have a tendency to impulsive buying behavior which can be proven through several aspects of impulsive buying. Respondents tend to lack consideration in planning the purchase of discounted goods and feel excited when they see discounted goods that they are interested in, thus encouraging them to make unplanned purchases. AbstrakSemakin majunya perkembangan zaman semakin maju pula perkembangan teknologi di dalamnya. Pesatnya perkembangan teknologi semakin memudahkan seseorang dalam mencari maupun memberi informasi terkini. Akibat dari perkembangan teknologi juga mempengaruhi perubahan cara individu dalam melakukan proses transaksi. Perkembangan teknologi dan akses internet lebih banyak digunakan oleh Gen Z. Muncul beberapa anggapan bahwa berbelanja secara daring lebih banyak memberi keuntungan daripada berbelanja secara langsung. Tujuan dari penelitian ini adalah mengetahui apakah discount promotion pada platform E-Commerce memiliki pengaruh terhadap impulsive buying dan untuk mengetahui dampak dari hal ini. Dalam penelitian yang dilakukan, penulis mengadopsi metode kualitatif dengan menggunakan teknik kuesioner terbuka untuk meninjau Gen Z yang menggunakan platform e-commerce untuk berbelanja. Hasil menunjukan bahwa responden memiliki kecenderungan perilaku impulsive buying yang dapat dibuktikan melalui beberapa aspek impulsive buying. Responden cenderung kurang memiliki pertimbangan dalam merencanakan pembelian barang diskon dan merasa senang saat melihat barang diskon yang mereka minati sehingga mendorong mereka untuk melakukan pembelian tak terencana.